Materiais híbridos contendo complexos de íons lantanídeos ligados covalentemente à superfície da sílica gel e luminescência sensibilizada por ligantes ß- Dicetonatos - Aguiar, Franklin Pessoa (2015)
This paper reports the preparation of novel organic-inorganic hybrid materials based on silica gel functionalized with silylating agents (3-aminopropyl) trimethoxysilane (APTS), [3-(2-aminoethylamine)-propyl]-trimethoxysilane (DAPTS) and 3-[2-(2-aminoethylamine) ethylamine] propyltrimethoxysilane (TAPTS) containing complexes ethylenediaminetetraacetate (EDTA) of lanthanide trivalent ions (Ln3+: Eu3+, Tb3+, and Gd3+) with luminescence sensitized by diketonates ligands: tenoiltrifluoroacetonate (tta), dibenzoilmetanate (dbm), benzoilacetonate (bzac) and acetylacetonate (acac). All materials were prepared by the heterogeneous route, in successive steps involving: i) functionalization of silica gel with various silylating agents, resulting in SilXN materials; ii) Modification of matrices functionalized with EDTA dianhydride forming SilXN-EDTA hybrids; iii) The adsorption of lanthanide ions, resulting in the SilXN-EDTALn systems; iv) Coordination of diketonate ligands to lanthanide ions. The new materials called as SilXN-EDTALn-dic, wherein X represents the number of nitrogen atoms in the chain silylating agent and dic refers to a diketonate ligand were characterized by elemental analysis, complexometric titration with EDTA, spectroscopy in the region of near Infrared (FT-IR), thermogravimetric analysis and diffuse reflectance in the UV-VIS region. The results showed that the functionalization processes and modification of silica gel were highly dependent on the nature of the silylating agent, being less efficient for systems with TAPTS. The presence of the ligands on the matrix was characterized by reflectance measurements whereas. The luminescent properties of the hybrid materials containing lanthanide ions and diketonate ligands have been investigated from spectral data of emission, excitation and decay curves, which were compared with those ones for precursor materials presenting water molecules acting as ligands SilXN-EDTALnH2O. All SilXN-EDTAEu-dic and SilXN-EDTATb-dic systems exhibited red and green luminescence when excited by UV radiation, respectively. In general, the processes of intramolecular energy transfer were more efficient for SilXN-EDTAEu-dic materials (for dic: tta and dbm) and SilXN-EDTATb-acac. Quantitative analysis of luminescent materials containing the Eu3+ ion were carried out on the basis of emission quantum efficiency data (n), experimental intensity parameters 2 and 4, Einstein’s spontaneous emission coefficients (A0J) and color coordinates (x,y) CIE. The results indicated that these parameters are sensitive to the type of silylating agent and diketonate ligands coordinated to the metal center, and systems with tta and dbm those who had the highest  values and purest colors, indicating that they are promising for applications such as phosphors.